2009
DOI: 10.1007/s10295-009-0652-6
|View full text |Cite
|
Sign up to set email alerts
|

The non-nutritional performance characteristics of peptones made from rendered protein

Abstract: Economic considerations require the use of inexpensive feedstocks for the fermentative production of moderate-value products. Our previous work has shown that peptones capable of supporting the growth of various microorganisms can be produced from inexpensive animal proteins, including meat and bone meal, feather meal, and blood meal, through alkaline or enzymatic hydrolysis. In this work, we explore how these experimental peptones compare to commercial peptones in terms of performance characteristics other th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…For example, peptones produced through enzymatic and alkaline hydrolysis of rendered animal protein including blood meal, meat and bone meal and feather meal to support the growth of microorganisms has been evaluated by Garcia et al (Garcia et al, 2010). Small peptides and amino acids have also been used as foliar fertilizers (Quartieri et al, 2002).…”
Section: Conversion Into Surfactants and Firefighting Foamsmentioning
confidence: 99%
“…For example, peptones produced through enzymatic and alkaline hydrolysis of rendered animal protein including blood meal, meat and bone meal and feather meal to support the growth of microorganisms has been evaluated by Garcia et al (Garcia et al, 2010). Small peptides and amino acids have also been used as foliar fertilizers (Quartieri et al, 2002).…”
Section: Conversion Into Surfactants and Firefighting Foamsmentioning
confidence: 99%
“…Clearly, the success of this strategy was limited. Further experimentation, reported elsewhere (Garcia et al, 2010), confirmed that approximately half of residual ash in solution consisted of calcium salts. Possibly, calcium that precipitated as calcium carbonate re-solubilized as calcium bicarbonate when the solution was neutralized.…”
Section: Proximate Analysis Of Protein Hydrolysatementioning
confidence: 57%
“…The hydrolysates have also been tested as feedstocks for industrial fermentations, substituting for expensive ingredients such as yeast extract or casamino acids. They were found to have favorable performance characteristics for this application (Garcia et al, 2010), and support the growth of the bacterium E. coli, the fungus Pythium irregular, and the alga Schizochytrium limacinum, in valuable-product-producing fermentation systems (manuscripts in preparation). The unhydrolyzed rendered meals are not effective in these applications.…”
Section: Discussionmentioning
confidence: 96%
“…3 The non-nutritional characteristics of the protein hydrolysates, such as hygroscopicity, chromicity, autoclave stability, viscosity, and foaming, were also reported; it is indicated that rendered proteins hydrolysate can be used as a low-cost substitute for commercial peptone. 4 All of these results demonstrate an opportunity for exploring animal proteins as a low-cost nutrition source for microorganism fermentation. This is particularly attractive for industrial fermentation focusing on commodity and moderatevalue products, as this type of fermentation process is characterized by a larger volume and being of moderate product value and more sensitive to the cost of growth medium ingredients.…”
Section: ' Introductionmentioning
confidence: 89%